A cadaveric study of anatomical variations of the radial nerve and their clinical significance - Aksić, Milan; Djurdjević, Katarina; Kapor, Slobodan; Puškaš, Laslo; Erić, Dražan; Stijak, Lazar; Aleksić, Dubravka; Aleksandrić, Dejan; Mališ, Miloš; Djulejić, Vuk (Vojnosanitetski pregled, 2023)
Background/Aim. The radial nerve (RN) is the largest terminal branch of the posterior cord of the brachial plexus. Upon leaving the axilla, the RN moves to the posterior compartment of the arm, where it makes close contact with the humerus. By penetrating the lateral intermuscular septum, RN enters the anterior compartment and, in the very proximity of the lateral epicondyle, divides into two terminal branches. The anatomy of this nerve is characterized by remarkable variability, the knowledge of which is of utmost importance in the fields of orthopedics and traumatology. The aim of the study was to examine the anatomy of the RN, including two parameters: the location and the way the RN divides into terminal branches, with a particular emphasis on the clinical implications of this data. Methods. The research was conducted on 27 cadavers, 15 female and 12 male, with a total of 54 upper extremities. After careful dissection, variations in the location and way of termination of the RN were observed on both the right and left hands. Collected data were then analyzed using Microsoft Office Excel. A classification where the division of the RN into terminal branches above the biepicondylar line (BEL) is defined as type A, while the division of RN below BEL is defined as type B was used. Results. According to the proposed classification, we observed a higher incidence of type A (66.7%) compared to type B (33.3%) in the total sample of 54 extremities. In addition, a higher prevalence of type A was observed in the female population, while a higher prevalence of type B was observed in the male population. There were differences in the distribution of types A and B between the left and right arms, but there were no variations in the way of termination of the RN. Conclusion. The present study showed an important complexity in the domain of RN anatomy with significant clinical implications. With that in mind, it is crucial for every patient that the limits of safe zones be defined while performing surgical procedures in the elbow to protect the RN and its branches from iatrogenic injuries.